Interface Engineering via Ti3C2Tx MXene Electrolyte Additive toward Dendrite-Free Zinc Deposition - Sun, Chuang; Wu, Cuiping; Gu, Xingxing; Wang, Chao; Wang, Qinghong (Nano-Micro Letters, 2021)
Zinc metal batteries have been considered as a promising candidate for next-generation batteries due to their high safety and low cost. However, their practical applications are severely hampered by the poor cyclability that caused by the undesired dendrite growth of metallic Zn. Herein, Ti3C2Tx MXene was first used as electrolyte additive to facilitate the uniform Zn deposition by controlling the nucleation and growth process of Zn. Such MXene additives can not only be absorbed on Zn foil to induce uniform initial Zn deposition via providing abundant zincophilic-O groups and subsequently participate in the formation of robust solid-electrolyte interface film, but also accelerate ion transportation by reducing the Zn2+ concentration gradient at the electrode/electrolyte interface. Consequently, MXene-containing electrolyte realizes dendrite-free Zn plating/striping with high Coulombic efficiency (99.7%) and superior reversibility (stably up to 1180 cycles). When applied in full cell, the Zn-V2O5 cell also delivers significantly improved cycling performances. This work provides a facile yet effective method for developing reversible zinc metal batteries. Highlights: 1 Well-dispersed MXene nanosheets in the electrolyte dramatically shorten Zn2+ diffusion pathways and facilitate their migration. 2 MXene interfacial layer with abundant functional groups and good conductivity induces uniform nucleation and enables long-term even deposition. 3 MXene-containing electrolyte realizes dendrite-free Zn plating/striping with high Coulombic efficiency (99.7%) and superior reversibility (stably up to 1180 cycles).